1997
DOI: 10.1093/emboj/16.4.739
|View full text |Cite
|
Sign up to set email alerts
|

Subunit change in cytochrome c oxidase: identification of the oxygen switch in Dictyostelium

Abstract: Cytochrome c oxidase (COX) has a complex modular structure in eukaryotes. Depending on growth conditions, interchangeable isoforms of selected subunits are synthesized and combined to the evolutionarily conserved catalytic core of the enzyme. In Dictyostelium this structural make‐up is regulated by oxygen and involves two forms of the smallest subunit, termed VIIe and VIIs. Here we show that, in spite of a considerable sequence divergency, they are encoded by adjacent genes, linked ‘tail to head’ by only 800 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Another way to adapt efficiently to a change in the growth conditions is by modifying the association of complexes as suggested recently for iron respiration in A. ferrooxidans [ 15 ]. In the case of the cytochrome c oxidase complex of Dictyostelium discoideum , the oxygen concentration induces a switch between two interchangeable subunit isoforms of the cytochrome c oxidase [ 84 - 86 ]. This switch has been shown to be due to transcriptional regulation and also to different stabilities of the two subunits toward oxygen [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way to adapt efficiently to a change in the growth conditions is by modifying the association of complexes as suggested recently for iron respiration in A. ferrooxidans [ 15 ]. In the case of the cytochrome c oxidase complex of Dictyostelium discoideum , the oxygen concentration induces a switch between two interchangeable subunit isoforms of the cytochrome c oxidase [ 84 - 86 ]. This switch has been shown to be due to transcriptional regulation and also to different stabilities of the two subunits toward oxygen [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the cytochrome c oxidase complex of Dictyostelium discoideum , the oxygen concentration induces a switch between two interchangeable subunit isoforms of the cytochrome c oxidase [ 84 - 86 ]. This switch has been shown to be due to transcriptional regulation and also to different stabilities of the two subunits toward oxygen [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the organism may be retooling some of its capacity for redox chemistry at the end of exponential growth. It is known that other organisms will exchange cytochrome C oxidase subunits to remain more metabolically versatile in response to changing redox state [ 33 ]. The other 12 genes include 6 putative genes which lack annotation ( vng0602C, vng1182H, vng1486H, vng2197H, vng2199H and vng2412H ), a putative putative haloacid dehalogenase-like hydrolase ( vng0719G ), a putative iron-sulfur cluster containing protein ( vng1184Gm ), a putative universal stress protein ( vng1898C ), a putative phosphoribosyl transferase ( vng1912G ), a heavy-metal transporting CPx-type ATPase ( vng2201G ) and an putative aminopeptidase ( vng2546G ).…”
Section: Resultsmentioning
confidence: 99%
“…In the slime mold Dictyostelium discoideum , there is an isoform pair of CcO subunit 7. Here, CcO7e, which is expressed under normoxic conditions, is replaced by CcO7s under hypoxia, and this switching is mediated by an oxygen‐dependent transcriptional element located in the short intergenic region between the two adjacent genes [26]. Analysis of the yeast and Dictyostelium CcO hypoxia‐regulated promoters revealed that the mammalian ORE sequence is absent in both organisms, which agrees with our functional model that the expression of CcO4‐2 represents a unique protective adaptation found in the highly oxygenated respiratory system in higher organisms, rather than being an adaptation to very low oxygen levels, under which yeast CcO5b and Dictyostelium CcO7s are expressed.…”
Section: Discussionmentioning
confidence: 99%